Rediscovery and re-description of Ischnocnema nigriventris (Lutz, 1925) (Anura: Terrarana: Brachycephalidae) - Berneck, Bianca V. M. [UNESP]; Targino, Mariane; Garcia, Paulo Christiano de Anchietta (Magnolia Press, 2013)
Besides its brief original description in 1925 and information provided by one specimen collected in the 1980s, nothing else is known for Ischnocnema nigriventris (Lutz, 1925). Also, the poor preservation of the type series has hindered the association of this name with any known population of Ischnocnema. Fieldwork in Bertioga municipality, state of São Paulo, Brazil, revealed a population of Ischnocnema to which we were able to apply the name Ischnocnema nigriventris. We report this rediscovery, re-describe the species on the basis of the newly found specimens, and describe its mating call. Ischnocnema nigriventris is allocated to the Ischnocnema lactea species series and we propose a diagnosis based on a combination of morphological character states. The species is diagnosed by prominent conical tubercles on the upper eyelid, inguinal region and hidden areas of the hind limbs with yellow mottling in males and orange mottling in females, and by its advertisement call composed of two to four non-pulsed notes, the first one differentiated from the others by its lower intensity and different frequency. Ischnocnema nigriventris is only known from Parque das Neblinas (Bertioga municipality), Paranapiacaba (Santo André municipality), and Boracéia (Salesópolis municipality), localities in the state of São Paulo, Brazil Copyright © 2013 Magnolia Press.
Keywords: Advertisement call; Brazilian Atlantic Forest; Ischnocnema; Natural history; Taxonomy